Rhythmic patterns, melodic outline and contour in ‘do I wanna know’ by arctic monkeys / Muhammad Yusuf Abd Ghani and Muhammad Haikal Yusri. - Abd Ghani, Muhammad Yusuf; Yusri, Muhammad Haikal (2020)
The purpose of this study is hoped to give contribution to the reader that they can know the structure of the song in terms of rhythmic pattern, melodic outline and contour. This research may be valuable for those who want to know deeper than their knowledge in understanding of rhythmic patterns, melodic outline and contour. The primary source for this study is from the analyzing the score by way transcribe the song. The findings shows that the song mostly use a simple repetitive rhythmic pattern but by using the technique of melodic embellishment and combination of several type of contour make the song more interesting and easy to remember. It can be a guide for composition students to expand their creativity in terms of music theory wise and writing a clear and creative line for the melody.